2022
DOI: 10.1002/ejoc.202101367
|View full text |Cite
|
Sign up to set email alerts
|

Triflic Imide‐Catalyzed Glycosylation of Disarmed Glycosyl ortho‐Isopropenylphenylacetates and ortho‐Isopropenylbenzyl Thioglycosides

Abstract: Glycosylation reaction involving the coupling of a glycosyl donor with a glycosyl acceptor is one of the cornerstones of chemical preparation of pure glycans and glycoconjugates of biological relevance. Catalytic glycosylation of glycosyl ester donors and thioglycosides is an attractive but underexplored topic in carbohydrate chemistry. Herein, triflic imide (Tf 2 NH)catalyzed glycosylation of various O-, S-, and C-nucleophiles has been achieved using disarmed glycosyl ortho-isopropenylphenylacetates (GIPPAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Glycosylation of 2d (46.6 mg, 0.06 mmol) with 3c (59 mg, 0.12 mmol) according to General Procedure 3 afforded 4f (51.2 mg, 84%, 1:1 α:β) as a colorless syrup. The crude product was purified through flash column chromatography: R f = 0.37 (4:1 hexane/EtOAc, v/v); 1 27 (m, 3H), 4.21 (dd, J = 7.9, 1.6 Hz, 1H), 4.12 (dd, J = 10.6, 3.6 Hz, 1H), 4.09−3.98 (m, 6H), 3.95 (dd, J = 10.0, 2.7 Hz, 1H), 3.88 (d, J = 2.5 Hz, 1H), 3.82 (dd, J = 9.7, 7.9 Hz, 1H), 3.77 (dd, J = 10.2, 3.8 Hz, 1H), 3.73 (dd, J = 10.6, 7.2 Hz, 1H), 3.69 (dd, J = 10.6, 7.4 Hz, 1H), 3.61−3.54 (m, 4H), 3.54−3.48 (m, 4H), 1.51 (s, 3H), 1.48 (s, 4H), 1.43 (s, 3H), 1.42 (s, 3H), 1.32 (s, 3H), 1.31−1.28 (d, J = 3.6 Hz, 10H); 13 ). Methyl 4-O-Benzyl-2,3-di-p-methyl-O-benzyl-6-O-(2,3,4,6-tetra-O-benzyl-D-glucopyranosyl)-α-D-galactopyranoside (4k).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycosylation of 2d (46.6 mg, 0.06 mmol) with 3c (59 mg, 0.12 mmol) according to General Procedure 3 afforded 4f (51.2 mg, 84%, 1:1 α:β) as a colorless syrup. The crude product was purified through flash column chromatography: R f = 0.37 (4:1 hexane/EtOAc, v/v); 1 27 (m, 3H), 4.21 (dd, J = 7.9, 1.6 Hz, 1H), 4.12 (dd, J = 10.6, 3.6 Hz, 1H), 4.09−3.98 (m, 6H), 3.95 (dd, J = 10.0, 2.7 Hz, 1H), 3.88 (d, J = 2.5 Hz, 1H), 3.82 (dd, J = 9.7, 7.9 Hz, 1H), 3.77 (dd, J = 10.2, 3.8 Hz, 1H), 3.73 (dd, J = 10.6, 7.2 Hz, 1H), 3.69 (dd, J = 10.6, 7.4 Hz, 1H), 3.61−3.54 (m, 4H), 3.54−3.48 (m, 4H), 1.51 (s, 3H), 1.48 (s, 4H), 1.43 (s, 3H), 1.42 (s, 3H), 1.32 (s, 3H), 1.31−1.28 (d, J = 3.6 Hz, 10H); 13 ). Methyl 4-O-Benzyl-2,3-di-p-methyl-O-benzyl-6-O-(2,3,4,6-tetra-O-benzyl-D-glucopyranosyl)-α-D-galactopyranoside (4k).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…20,21 Though modified NPGs were developed, 22−26 they still require stoichiometric halonium ion activation and a catalytic version is yet to be developed. 27 activatable donors but also cannot be used for all kinds of glycosylations, particularly for the synthesis of S-linked glycosides that might react with the promoter. S-Linked glycosides 12 are biologically important as members of this class of compounds are resistant to enzymatic hydrolysis and can retain the biological properties of glycans.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au(I)-or Cu(II)-catalyzed glycosylation with thioglycosides as donors has been independently reported by Yu, 10 Zhu, 11 Zhang, 12 and Sun. 13 In regard to the metal-free catalytic glycosylation, Ragains 14 and Li 15 have respectively demonstrated that the glycosylation can be realized in the presence of Bronsted acids. Although breakthroughs have been achieved in catalytic activation of thioglycosides, the development of an efficient and catalytic glycosylation is still highly in demand with a readily accessible and easy-to-handle thioglycoside donor, especially a thioglycoside donor that can be catalyzed under metal-free conditions and enable effective glycosylation with a broad substrate scope.…”
mentioning
confidence: 99%
“…As shown in Scheme , thioglycoside 1f , a monosaccharide, was converted into β-acyl glycoside 2p , the formation of which was confirmed by TLC. The reaction with thioglycoside-derived glycosyl acceptor 3a was performed with the addition of an equivalent amount of BF 3 ·Et 2 O or TMSOTf, which is used as the activator of glycosyl esters; however, only low yields of the disaccharide were obtained. The yield improved substantially using a catalytic amount of tris­(pentafluorophenyl)­borane [B­(C 6 F 5 ) 3 ] as a Lewis acid, , which has been recently used in glycosylation as an activator of glycosyl acceptors.…”
mentioning
confidence: 99%